THE INFLUENCE OF PEER INTERACTION AND PRACTICE FREQUENCY ON ENGLISH VOCABULARY MASTERY AT MTS MIFTAHUL ULUM KEBUN WANGI - Moh Rofiki; Sujito (PT Wahana Global Education, 2025)
This research investigates the impact of peer interaction and practice frequency on the English vocabulary mastery of eighth-grade students at MTs Miftahul Ulum Kebun Wangi. Employing a quantitative correlational approach, the study involved 48 participants selected through simple random sampling. Data were collected using two instruments: a Likert-scale questionnaire measuring peer interaction and practice frequency, and a 30-item vocabulary test assessing students’ lexical knowledge. The results of the descriptive analysis indicated mean scores of 3.40 (SD = 0.61) for peer interaction, 3.15 (SD = 0.68) for practice frequency, and 72.7% (SD = 11.9) for vocabulary mastery. Correlation analysis revealed a significant positive relationship between peer interaction and vocabulary mastery (r = 0.52, p < 0.001), as well as between practice frequency and vocabulary mastery (r = 0.60, p < 0.001). Furthermore, multiple regression analysis showed that both independent variables jointly accounted for 46% of the variance in vocabulary mastery (R² = 0.46, F(2,45) = 19.1, p < 0.001), with standardized beta coefficients of 0.34 for peer interaction and 0.41 for practice frequency. The findings highlight that collaborative peer engagement and consistent practice significantly enhance students’ vocabulary acquisition. It is therefore recommended that English teachers integrate peer-based and practice-oriented strategies to strengthen students’ lexical development.